2018
DOI: 10.1002/cpp.2339
|View full text |Cite
|
Sign up to set email alerts
|

Clients' experience of change: An exploration of the influence of reformulation tools in cognitive analytic therapy

Abstract: Case formulation is considered important in both the development of the therapeutic relationship and in starting the process of therapeutic change. Cognitive analytic therapy (CAT) describes the developmental origins and maintenance of a client's problems in both written (reformulation letter) and diagrammatic form (sequential diagrammatic reformulation). This study aimed to investigate the effects of these reformulation tools on insight and symptom change. A small‐N repeated measures design was employed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…Of note, one of the least helpful treatment components rated by clients involved the completion of the reformulation letter. Regarding the reformulation letter, findings from the current study are somewhat inconsistent with findings reported by Tyrer and Masterson (2019) who indicated that clients in their sample reported the benefit of the reformulation letter in helping to note re‐enactments although this did not necessarily lead to significant change on levels of insight or symptom reduction. The actual additive benefits of reformulation tools have been brought into question as regard clinical effectiveness and may be largely redundant amongst those accessing a primary care level intervention (Kellett et al ., 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…Of note, one of the least helpful treatment components rated by clients involved the completion of the reformulation letter. Regarding the reformulation letter, findings from the current study are somewhat inconsistent with findings reported by Tyrer and Masterson (2019) who indicated that clients in their sample reported the benefit of the reformulation letter in helping to note re‐enactments although this did not necessarily lead to significant change on levels of insight or symptom reduction. The actual additive benefits of reformulation tools have been brought into question as regard clinical effectiveness and may be largely redundant amongst those accessing a primary care level intervention (Kellett et al ., 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…Five studies investigated service users’ experience of CAT Tools (Hamill, Ried & Reynolds, 2008; Rayner, Thompson, & Walsh, 2011; Stockton, 2012; Taplin, 2015; Tyrer & Masterson, 2019). One study focused on the experience of CAT tools in general (Rayner et al ., 2011), two focused on letters (Hamill et al ., 2008; Stockton, 2012), one on sequential diagrammatical reformulations (Taplin, 2015), and one on reformulation tools (Tyrer & Masterson, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies focused on service users with a range of mental health diagnoses and difficulties (Fusekova, 2011; Rayner et al ., 2011; Tyrer & Masterson, 2019) and eight on service users with particular diagnoses, including personality disorders (Kellett et al ., 2013; Kellett & Hardy, 2014), depression (Sandhu et al ., 2017; Stockton, 2012), panic disorder (Tzouramanis et al ., 2010), psychosis (Taylor et al ., 2019), Axis 1 disorders (Shine & Westacott, 2010), and anxiety and depression (Hamill et al ., 2008). Ruppert (2013) and Taplin (2015) included service users defined as having significant mental health problems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations